THE INFLUENCE OF BRAND IMAGE, PRODUCT INNOVATION AND BRAND TRUST ON THE COMPETITIVENESS OF WARDAH COSMETIC PRODUCTS ON STUDENTS OF THE NATIONAL UNIVERSITY OF JAKARTA - Yonandia Febriyani; Suadi Sapta Putra; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This research aims to analyze and determine the influence of Brand Image, Product Innovation and Brand Trust on the Competitiveness of Wardah Cosmetic Products among Students at the National University of Jakarta. The data source used in this research uses primary data in the form of a questionnaire. This research data was given to 100 sample respondents, namely Jakarta National University students who had purchased and used Wardah cosmetic products at least once. In this research, sampling was used using the purposive sampling method. Data were processed using SPSS with data analysis techniques used, namely descriptive analysis and multiple linear regression, to test research instruments using validity and reliability tests, classical assumption tests using normality, multicollinearity, heteroscedasticity and autocorrelation tests. Hypothesis testing uses the f test, t test and coefficient of determination. Based on the research results, Brand Image has a positive and insignificant effect on Competitiveness, Product Innovation has a positive and insignificant effect on Competitiveness, and Brand Trust has a positive and significant effect on Competitiveness.